2019
DOI: 10.1136/rmdopen-2019-001037
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage-gut-microbiome axis: a new paradigm for novel therapeutic opportunities in osteoarthritis

Abstract: DNA of gut microbiota can be found in synovium of osteoarthritis and rheumatoid arthritis. This finding could result from the translocation of still alive bacteria from gut to joints through blood, since the diversified dormant microbiota of healthy human blood can be transiently resuscitated in vitro. The recent finding of gut microbiome in human cartilage, which differed between osteoarthritis and controls, suggests that a similar trafficking of dead or alive bacteria from gut microbiota physiologically occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 58 publications
1
52
0
1
Order By: Relevance
“…While we did not seek to explore FGIDs in other rheumatic or musculoskeletal conditions, these groups are often used in comparison to fibromyalgia. Interestingly, we found higher rates of IBS in subjects with other rheumatological conditions compared to healthy controls further supporting an interaction between the gut microbiota and the musculoskeletal system (66,67). Sperber et al (32) reported that fibromyalgics with IBS had worse symptoms of fatigue, morning tiredness and pain, compared to those without IBS.…”
Section: Discussionsupporting
confidence: 72%
“…While we did not seek to explore FGIDs in other rheumatic or musculoskeletal conditions, these groups are often used in comparison to fibromyalgia. Interestingly, we found higher rates of IBS in subjects with other rheumatological conditions compared to healthy controls further supporting an interaction between the gut microbiota and the musculoskeletal system (66,67). Sperber et al (32) reported that fibromyalgics with IBS had worse symptoms of fatigue, morning tiredness and pain, compared to those without IBS.…”
Section: Discussionsupporting
confidence: 72%
“…This correlation has been described in rodent models and humans affected by OA and is characterized by increased levels of circulatory inflammatory markers including bacterially produced lipopolysaccharides (LPS) [36,37], suggesting that microbiome-derived proinflammatory metabolites could play a putative role in OA pathogenesis. Moreover, it has recently been shown that the subchondral dysbiosis resulting from the bacterial translocation from GM to the joint, might support the development of OA [14]. Therefore, considering gut dysbiosis and the leaky gut syndrome as cofactors in the development of inflammaging and consequently of OA [38], it is likely to hypothesize the existence of a 'gut-joint axis' [7,[14][15][16]].…”
Section: Inflammagingmentioning
confidence: 99%
“…Moreover, it has recently been shown that the subchondral dysbiosis resulting from the bacterial translocation from GM to the joint, might support the development of OA [14]. Therefore, considering gut dysbiosis and the leaky gut syndrome as cofactors in the development of inflammaging and consequently of OA [38], it is likely to hypothesize the existence of a 'gut-joint axis' [7,[14][15][16]].…”
Section: Inflammagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, an emerging concept of gut-joint axis has associated the gut dysbiosis (perturbation of gut microbiota (GM) biodiversity and function), and the leaky gut syndrome with the joint disease progression [42,43]. In both human and rodent model, an increase in serum level of the pro-inflammatory marker and bacterial metabolites were associated with OA severity [44,45].…”
Section: Discussionmentioning
confidence: 99%